The Family, Inheritance, and the Intergenerational Transmission of Inequality - Tomes, Nigel (Journal of Political Economy, 1981)
Unequal inheritance of material wealth is commonly considered a major cause of inequality in consumption. However, theoretical models of the intergenerational transmission of inequality by Becker, Blinder, and Ishikawa imply that unequal inheritance may either increase or reduce consumption inequality. Differences in inherited wealth resulting from unequal parental incomes increase inequality in recipients' consumption. However, unequal bequests caused by differences among families in the endowed ability of children or the costs of producing human capital are equalizing. Empirical results confirm these predictions: The inheritance received by children is inversely related to both children's income and parental education. Thus bequests are "compensatory" in that (ceteris paribus) low-income children inherit more than their advantaged contemporaries.